Quality Control Circle Activities Improve Nurses'Accuracy of Morse Fall Risk Assessment Scale (English Translation). (2021) - Miao-chun, LIN; Li-ping, CHEN; Yong-juan, WU; Yu, LI; Lu-qing, CHEN; Xiao-xia, LIN; Qiao-qiao, CHEN; Wei-ping, XU
No abstract available